PENDETEKSIAN IKAN BANDENG BERFORMALIN MELALUI CITRA MATA MENGGUNAKAN ALGORITMA k-NEAREST NEIGHBOR (kNN) - Niko Aldino (2020)
Fish is a source of animal food ingredients that contain nutrients and proteins that are good for the body. Fish that are good for the body are fish that have not been mixed with chemicals or preservatives, any of the preservatives used in fish is formalin. Formalin when used in the long time can cause poisoning in the human body, causing digestive disorders and in the long run it will cause cancer in the body. Based on thes the purpose of this study was to identify fish containing formalin and not containing formalin through eye image using HSV (Hue, Saturation, Value) color feature extraction and using the k-Nearest Neighbor (kNN) algorithm to help the digital image processing. The results of this study are the level of accuracy for detecting formalin and non-formalin fish eye images. With the kNN method an accuracy of 80% was obtained in the k = 1 and k = 3 experiment.